Examining bushfire policy in action: Preparedness and behaviour in the 2009 Black Saturday fires. Issue 63 (September 2016) - Handmer, John; O'Neill, Saffron
Highlights: Study examines preparedness and behaviour in the face of an extreme bushfire event. Method uses unique fatality dataset comprising police, forensic and other records. Preparation for bushfire requires triggers for action and contingency plans. Understanding preparedness to defend is important in case evacuation becomes unsafe. Community bushfire policy remains challenging, especially under climate change. Abstract: An important part of reducing the risk of disaster is the preparedness of the people at risk. Australian bushfire authorities have policies and publicity about what households should do to be prepared – which include knowledge about fire risk, awareness of one's own risk, taking specific steps to reduce risk including having an emergency plan. Yet, there is sparse empirical evidence about the link between preparedness and actual behaviour in the face of a major disaster. The authors had an opportunity to examine the circumstances surrounding the 172 civilian fatalities which occurred in the 2009 Victorian 'Black Saturday' bushfires, through the examination of a detailed fatality dataset compiled by the Victorian Bushfires Royal Commission. This dataset allows detailed examination of Victorian bushfire safety policy ('Stay or go') in action on a day of extreme fire danger: from preparedness (both before and on the day of the fire) to behaviour on the day of the fire itself. This analysis presents three overarching findings. First, some aspects of 'Stay or go' appear to be supported: being well-prepared to evacuate remains the safest option in a bushfire; sheltering passively is very dangerous. Second, successful implementation of 'Stay or go' depends on a multitude of factors, which can challenge even the most capable householders. Third, events like Black Saturday challenge the 'Stay or go' approach, and indicate the need for a different approach on extreme fire danger days. We conclude by reflecting on the findings from this research in terms of the most recent changes to bushfire policy in Victoria.